An intelligent and secure smart watering system using fuzzy logic and blockchain. (July 2019) - Munir, M. Safdar; Bajwa, Imran Sarwar; Cheema, Sehrish Munawar
Abstract: An intelligent Smart Watering System (SWS) is presented in this paper that is assisted with an Android application for smart consumption of water in small are medium-scale garden and fields. The proposed system banks on a set of accessible and economical sensors that capture real-time data of plants and environment conditions such as Soil Moisture Level, Light Intensity, air humidity, air temperature, etc. Once the data is collected from sensors on a server, the proposed SWS processes the data to decide about the watering schedule using Block-chain and Fuzzy Logic approach. Here, Fuzzy Logic approach helps in taking smart decisions with respect to watering requirements and Block-chain provides the required security in IoT enabled system by allowing only the trusted devices to access and manage the proposed SWS. In our approach, Blockchain technology plays an important role by providing scalability, privacy, and reliability in the proposed IoT base smart system. The multiple users and devices can be involved in monitoring and interacting remotely with plants by using Smart Watering System (SWS) (prototype) application that is developed in Android. Once the Fuzzy Logic based system decides the action on the bases of values of the input variables, the SWS activates the actuators to take watering actions such as turning water tunnels ON/OFF in periodical manner. The results of the proposed system show that it is efficient and secure application to efficiently handle the watering process of plants.